Population Dynamics of Bemisia tabaci Genn. and Type of Predators Found on the Edamame Soybeans (Glycine max L.) in Mangli Jember - Wijayanto, Tulus; Sudarmadji, Sudarmadji; Purwatiningsih, Purwatiningsih; Purnomo, Hari (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
The study was conducted at the edamame plantation area of PT. Mitra Tani 27 Jember with the size of 31.6 m x 29.8 m. The sampling of imature B. tabaci was done by collecting the samples of leaves from the five plots of planting. The adult samples were taken by setting some yellow traps with the size of 20 x 30 cm. The results showed that the populations of B. tabaci changed during the growing season of edamame, the older the plants grow, the greater number of the populations. The highest number of B. tabaci adult population was in the age of 10 weeks after planting, those were 818 B. tabaci. The increase of the B. tabaci population had a significant correlation with the increase of the predators population on edamame. There were seven species of predators founded at the edamame. The highest number of predator founded was Coccinella transversalis and the lowest number of predator was Coccinella septempunctata. Keywords: Bemisia tabaci Genn., edamame Soybeans, yellow traps, C. transversalis